„Mowa dziejów, mądrość poezji. Szkice” – nowa książka prof. dra hab. Gustawa Ostasza - Ożóg, Zenon (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The author of the review presents and evaluates Gustaw Ostasz’s book. He draws attention to the multitude of articles it contains and their diversity: there are sketches, reviews, studies - analyzes and interpretations of poems, as well as reflections on the achievements of selected writers. The author recommends the book to students, teachers and literary researchers.
Keywords: writers; poets; history; interpretation of literary works